Pemanfaatan Obat Bahan Alam Untuk Menjaga Imunitas Tubuh Berdasarkan Kajian Etnobotani Dan Thibbun Nabawi - Muhith, Abd.; Fitrah Dewi, Rosita; Hidayati, Nor; Syawiril Ammah, Erisy; Jauhari, Jauhari; Fathkul Wahab, Abdillah (Al-Hikmah: Jurnal Agama dan Ilmu Pengetahuan, 2022)
Indonesia has 9.47% of the total plant species in the world. Plants of various kinds are a gift from God to be chosen and used as a cure for many diseases. The high biodiversity of plants also supports the development of traditional elements of society which are reflected in their use, especially as medicines. This study aims to explain the use of traditional medicine to maintain the immune system from ethnobotany and thibbun nabawi. This type of research is descriptive qualitative research involving key informants. The data was obtained by snowball sampling and analyzed by inductive technique. This study revealed that the people of Tiris used 18 types of natural medicines to maintain body immunity during the pandemic. People also used other minerals such as honey, eggs, and eucalyptus oil for herbs. The highest used value (UV) is 0,70, namely temu kunci (Boesenbergia pandurata), and the result of calculating the ICF value for this natural medicine is 0,68. This utilization is an effort to deal with a pandemic by thibbun nabawi, using herbs and honey.